Khasiat Buah Tin (Fiscus carica L.) dalam Perspektif Al-Qur’an dan Sains - Ramadhanti, Nova (Es-Syajar:Journal of Islam, Science and Technology Integration, 2023)
The fig fruit plant (Ficus carica L.) is a type of plant that belongs to the Moraceae family which has a specialty in the Qur'an and is rich in benefits and grows a lot in the West Asia region and of course Indonesia. In Indonesia, the existence of figs has begun to be developed to be varied into products that can compete in the market. Figs are specifically enshrined in the Qur'an which is in the letter at-Tiin, this means that Allah hints at the efficacy or benefits of figs. The content of bioactive compounds in figs can be used as medicine and is useful for treating various diseases. In addition to bioactive compounds, the largest chemical content is in figs, namely polyphenols and flavonoids. The purpose of writing this journal is to provide information regarding the properties and benefits of figs. The properties contained in figs are also used for traditional medicine, including being used for the treatment of ulcers, indigestion and diarrhea, while in the scientific scope and pharmacological activity including as an antibacterial, antioxidant, antitumor, and anti-inflammatory agent.